Synthesis and catalytic activity of Ti-MCM-41 nanoparticles with highly active titanium sites - Lin, Kaifeng; Pescarmona, Paolo P.; Vandepitte, Hans; Liang, Duoduo; Van Tendeloo, Gustaaf; Jacobs, Pierre A. (Journal of catalysis, 2008)
Ti-MCM-41 nanoparticles 80–160 nm in diameter (Ti-MCM-41 NP) were successfully prepared by a dilute solution route in sodium hydroxide medium at ambient temperature. Ti-MCM-41 NP were characterized by X-ray diffraction, nitrogen adsorption/desorption isotherms, SEM, TEM, FT-IR, and UV–vis spectroscopy. The characterization results showed the existence of highly ordered hexagonal mesoporous structure and tetrahedral Ti species in Ti-MCM-41 NP. In the epoxidation of cyclohexene with aqueous H 2O 2, Ti-MCM-41 NP displayed higher conversion and initial reaction rate than a Ti-MCM-41 sample with normal particle size (Ti-MCM-41 LP). Diffusion of the reactants was accelerated and the accessibility to the catalytic Ti species was enhanced in the shorter channels in Ti-MCM-41 NP samples. Ti-MCM-41 NP showed much higher selectivity for cyclohexene oxide compared with Ti-MCM-41 LP, suggesting reduced hydrolysis of cyclohexene oxide with water in the former case. The increased selectivity for cyclohexene oxide can be attributed to the lower concentration of residual surface silanols in Ti-MCM-41 NP and the shorter residence time of epoxide in the shorter mesoporous channels. Ti-MCM-41 NP also appears to be a suitable catalyst in the epoxidation of a bulky substrate, like cholesterol, with tert-butyl hydroperoxide.